Improving Mobility and Reducing Disability in Older People Through Early High-Dose Vitamin D Replacement Following Hip Fracture: A Protocol for a Randomized Controlled Trial and Economic Evaluation - Mak, Jenson C. S. (SAGE Publications, 2011)
Hypovitaminosis D is particularly common among older people with a proximal femoral (hip) fracture and has been linked with poorer lower extremity functioning, falls, and fractures. There is evidence that disability severity and fall rates may be reduced by adequate vitamin D replacement. However, the ideal regimen for vitamin D administration to have these benefits in older people who have been in the hospital has not been established. This randomized controlled trial will investigate the effects of an oral vitamin D loading dose with maintenance oral vitamin D and calcium on lower extremity function (gait velocity), correction of hypovitaminosis D, falls, and fractures among older people after hip fracture surgery. The cost-effectiveness of the REVITAHIP program from the health and community service provider’s perspective will also be established, as will predictors of adherence with the treatment. A total of 450 older people who have recently had a hip fracture requiring surgical intervention will be screened to achieve 250 participants for the study. Participants will have no medical contraindications to vitamin D replacement. The primary outcome measure will be mobility-related disability as measured with the 2.4-m gait velocity test. Secondary measures will be 25-hydroxyvitamin D (25-OHD) levels at 2, 4, and 26 weeks, number of falls and fractures, and additional measures of mobility, disability, quality of life, health system and community–service contact, adherence to the intervention, and adverse events. After surgical fixation and being deemed medically stable, participants will be randomly allocated to an intervention or placebo-control group. Participants of the intervention group will receive initial oral 250 000 IU (5 × 50 000 IU) vitamin D3 tablets. Both groups will receive oral maintenance vitamin D3 and calcium and will follow the usual hip fracture rehabilitation pathway. The study will determine the impact of a vitamin D loading dose on mobility-related disability in older people following hip fracture and will discuss the efficacy and cost-effectiveness of a loading dose vitamin D replacement more generally. The results will have direct implications for future use of vitamin D therapy for this high-risk group.